Effect of the resin content and density on the properties of three layer particleboard from kelempayan (neolamarckia cadamba) and wood shaving / Abdul Halim Mohd Hatta - Mohd Hatta, Abdul Halim (Faculty of Applied Sciences, 2015)
Particleboard are composite panel product consisting of cellulosic particle of various size that are bonded together with a binder or synthetic resin under heat and pressure. The species of kelempayan (Neolamarckia cadamba) with diameter 40 cm at breast height (DBH) 25 m height, from 1 log diameter was converted into particle by using scale knife ring flaker. The target density were 500 kgm·3, 600 kgm·:; and 700 kgm·3. The particleused in this process were unscreening and was further dried to a certainmoisture content. The particleboard were produced in different densities, resin contents; 8%, 10% and 12% with addition of 1% wax with usingadhesive urea formadehyde (UF). The particleboards were tested to determine the physical properties of particleboard according to JIS 2003. From the variance densities shows highly significant on modulus of rupture (MOR), internal bonding (18) and water absorption (WA).Meanwhile, for modulus of elasticity (MOE) and thickness swelling (TS) were significant. Source of variance from resin content showed the highly significant on internal bonding and thickness swelling but for modulus of rupture, modulus of elasticity (MOE) and water absorption (WA) that are only significant. The mechanical properties, from particleboard on density 700 kgm·3 with resin content 8%, 10% and 12% were achieved the standard. On physical properties, particleboard density 500 kgm·3with resin content 10% and 12% were achieved the JIS 2003 specification. Whereas, for resin content, impact can be observed only on modulus of rupture (MOR), thickness swelling (TS) and water absorption (WA).